2020
DOI: 10.1038/s41398-020-0781-2
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning classification of ADHD and HC by multimodal serotonergic data

Abstract: Serotonin neurotransmission may impact the etiology and pathology of attention-deficit and hyperactivity disorder (ADHD), partly mediated through single nucleotide polymorphisms (SNPs). We propose a multivariate, genetic and positron emission tomography (PET) imaging classification model for ADHD and healthy controls (HC). Sixteen patients with ADHD and 22 HC were scanned by PET to measure serotonin transporter (SERT') binding potential with [ 11 C] DASB. All subjects were genotyped for thirty SNPs within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…Studies explicitly based on self-rating scales could not be found which stresses the importance for further research in this area. Connecting the literature to our analyses, we conclude that research groups in the area of ADHD relied predominantly on SVM, however the Random forest approach was also used 29 . It is known that in some challengeable cases GBMs may outperform Random Forest models.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Studies explicitly based on self-rating scales could not be found which stresses the importance for further research in this area. Connecting the literature to our analyses, we conclude that research groups in the area of ADHD relied predominantly on SVM, however the Random forest approach was also used 29 . It is known that in some challengeable cases GBMs may outperform Random Forest models.…”
Section: Discussionmentioning
confidence: 88%
“…In a visual GO/NOGO task, special ERP components were able to differentiate between adult ADHD subjects and controls with an accuracy of 92% using SVM with tenfold cross-validation 28 . Evaluating PET imaging and genetic predictors within the serotonergic system, an accuracy of .82 could be achieved for classification of ADHD and controls using Random Forest with fivefold cross-validation 29 . The Random Forest approach was used to investigate how multiple genetic and environmental factors jointly contribute to ADHD, or to examine whether hyperactivity persists in male and female adults with ADHD 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…This disadvantage is not elaborate along with external validation. Although there are some reports without the external dataset [13,19,23,24], the performance of our DLA should be assessed using an independent external validation dataset to validate our results in the future. Second, this cohort included only patients that were referred to the study center with suspected AIS [4,10].…”
Section: Discussionmentioning
confidence: 99%
“…All data in the validation dataset were independent of the files in the training dataset. The shuffling into five datasets and five-fold cross validation was conducted 10 times in this process [19].…”
Section: Input Datamentioning
confidence: 99%
“…Future studies could greatly benefit from the use of high-throughput genotyping/sequencing for the identification of putative causal variants underpinning perceptual organization in ADHD, leading to the identification of genetic profiles better responding to specific ADHD treatments and the development of translational medicine approaches [180,181]. Furthermore, these variants could also be used for developing predictive models, based on machine learning and artificial intelligence [182][183][184], for ADHD diagnosis and the identification of severe ADHD cases [97,115,120,185] in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%